Nickel-Catalyzed Reductive Cross-Coupling of Vinyl Bromides with Unactivated Alkyl Halides - Gu, Jun; Qiu, Canbin; Lu, Wenbin; Qian, Qun; Lin, Kunhua; Gong, Hegui (Synthesis, 2017)
The use of pyridine as the sole ligand for the reductive vinylation of unactivated secondary alkyl halides under Ni-catalyzed conditions has been developed. Both alkyl- and aryl-substituted vinyl bromides are suitable, in which alkyl-decorated α-alkenyl bromides resulted in the α-products in good results.
Keywords: nickel; cross-coupling; arylation; alkyl halide; catalysis